Investigation of the antimicrobial efficacy and cytotoxicity of a natural disinfectant Syzygium cumini (L.) skeels leaf extract on vero cell lines - Haorongbam Joldy Devi, Prathiba Gnanasekaran, Yumnam Asha Devi, Durairaj Siva, Jaihitashee Jayashankar (Journal of Applied Pharmaceutical Science, 2024)
Disinfectants are vital for infection prevention and environmental health maintenance. However, the use of chemical disinfectants has adverse effects on human health, including the development of antibiotic-resistance genes and resistance to disinfectants due to overuse and abuse. There is a critical need to find natural alternatives to reduce the problems caused by chemical disinfectants. The present study analyzed the antimicrobial activity of Syzygium cumini leaf extract (SCLE) against Staphylococcus aureus, Pseudomonas aeruginosa, Mucor sp., Candida albicans, and Aspergillus niger and its efficacy as a natural disinfectant was also evaluated, along with GC-MS analysis and in vitro toxicity test. The study showed that SCLE exhibited antimicrobial activity against all test organisms except A. niger. The minimum inhibitory concentration (MIC) against S. aureus, P. aeruginosa, Mucor sp., and C. albicans was 625, 1,250, 78, and 1,250 μg/ml, respectively. The minimum bactericidal concentration (MBC) against S. aureus and P. aeruginosa was 1,250 and 2,500 μg/ml, respectively. The minimum fungicidal concentration (MFC) against Mucor sp. and C. albicans was 156 and 5,000 μg/ml, respectively. SCLE demonstrated bactericidal and fungicidal properties based on MIC: MBC and MIC: MFC, with significant reductions in P. aeruginosa (99.99%), S. aureus (90.71%), Mucor sp. (92%), and C. albicans (73.45%) after the treatment. Syzygium cumini leaf extract, identified as nontoxic with an IC50 of 320μg/ml, proves promising as a potent natural disinfectant. This study marks the first report on the efficacy of S. cumini leaf extract against test organisms, showcasing its potential as a natural disinfecting agent against test organisms.
Keywords: Syzygium cumini, bactericidal, fungicidal, natural disinfectant, GC-MS analysis, in vitro toxicity test